KARLSRUHE-LUXEMBOURG: A NEW DISTANCE AFTER THE 2009 LISBON TREATY RULING - Astengo, Francesca (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2012)
The 2009 decision on the ratification of the Lisbon Treaty by the German Federal Constitutional Court (FCC) is a landmark ruling on European integration. According to the FCC, the Lisbon Treaty is compatible with the German Basic Law because it does not lead to the creation of a European State.Despite the presence of some continuity with the previous jurisprudence on German participation in the EU, the Lisbon ruling took some of the arguments to a new level with regard to national sovereignty and the limits of European integration. This article highlights the elements of the decision which were set on a path of collision with the interpretations of the European Court of Justice marking an increased distance between Luxembourg and Karlsruhe.